EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN KELAPA SAWIT DI DESA ENGKASAN KECAMATAN TAYAN HULU KABUPATEN SANGGAU - Iyus Iyus; Asmahan Akhmad; Ary Krisnohadi (Fakultas Pertanian Universitas Tanjungpura, 2021)
This study aims to determine the level/grade suitability of land for oil palm plantations and attempt to provide management recommendations. Results of land evaluation, whether the results obtained from the field and the results of laboratory analysis results will provide information and guidance necessary land use and finally value of production expectations increased. The research was conducted in the village of Engkasan Tayan Hulu subdistrict Sanggau district with an area of 100 hectares. Analysis of soil samples carried out in the Laboratory of Chemistry and Soil Fertility Faculty of Agriculture, University Tanjungpura Pontianak. The study started from April 2015 until the end of April 2016. The research was conducted by survey method using a grid system. Implementation of the research include: 1) Preparation, consisting of cartography topography of the site of research, collecting secondary data research sites and tools and materials used, 2) field observations, consisting of drilling and profiling of land, 3) Analysis soil samples in the laboratory, 4) Analysis and compilation of data, which consists of determining ratings soil chemical properties, determining the nomenclature of land, determination of land suitability classes, determination of the limiting factors of land, 5) Interpretation of the data and presenting the results, the data obtained in the field associated with the results of the analysis in the laboratory.The interpretation of field data and analysis in the laboratory showed that among the sites there are 4 Soil Mapping Unit, but it has one type of soil and is classified into the Order Ultisol, Sub-order Udik, Great-group Kandiudults, Sub-order Typic Kandiudults with epipedon ocric and horizon diagnostic kandik. Soil Mapping Unit 1 has a land suitability classes S3-n (nutrient status) actual and potential land suitability classes S1, Soil Mapping Unit 2 has a land suitability classes S3-ns (slope and nutrient status) actual and potential land suitability classes S1, Soil Mapping Unit 3 has the actual land suitability classes N1-s (slope). N1-s (slope) can not do so any improvement potential land suitability classes Soil Mapping Unit remain N1-s (slope) 3 and Soil Mapping Unit 4 has the actual land suitability classes N2-s (slope). N2-s (slope) can not do so any improvement potential land suitability classes Soil Mapping Unit remain N2-s (slope). Recommended management consists of organic materials recommendation, liming, fertilizing and terracing. The results of the lime requirement calculations amounted to 0.5344 ton / mgCa (CO3) 2 / ha, the result of calculation of P and K fertilizer demand respectively 159.8 kg / ha SP36 and 130 kg / ha KCl.